The Social and Humanitarian Impact of the National Navy's Support Days - Barrera-González, Julián G.; Parrado-Molano, Cristian D.; Santacruz-Montano, Alirio A.; Serrano-Flórez, Marlon A. (EFIM Ediciones, 2023)
Development support is fundamental for members of military institutions today, in the sense that these actions are based on the belief that sustainable development and the improvement of the quality of life of local communities are essential for national stability. This is why the impact of the Development Support Days, carried out by the National Navy's Integral Action Group in Colombia, is analyzed, highlighting the importance of addressing the underlying causes of conflicts and building trust between the military forces and the civilian population. From a legal and normative perspective, these days comply with human rights and international obligations governing the actions of military forces in civilian situations. In practice, they translate into the provision of essential services, such as medical care and education, as well as support for economic development and infrastructure projects. These concrete actions, such as building schools and supporting agricultural projects, improve the quality of life of local communities and promote stability and cooperation. In summary, these activities reflect the National Navy's commitment to the development and well-being of Colombia, generating an environment conducive to peace and the strengthening of relations between the military and the civilian population.